Community Willingness and Readiness for Cultural Heritage Tourism: The Case of Kampung Chitty, Malacca Historic City, Malaysia - A. Rahman, Muhammad Ali; Mahamad Najib, Nurul Najwa (IIUM PRESS, 2025)
Cultural heritage tourism (CHT) engages communities by preserving and showcasing traditions, identities, and practices. Cultural heritage tourism involves traveling to explore places, artifacts, and activities that reflect a region’s historical narratives and identity. It encourages local communities to engage by sharing their heritage and traditions. However, successful cultural heritage tourism depends on the willingness and readiness of the local community to participate. Despite its significance in sustainable tourism planning and heritage preservation, research on local community participation remains limited. This study investigates the willingness, readiness, and involvement of Kampung Chitty residents in Malacca’s heritage tourism. Using a qualitative approach, five semi-structured interviews were conducted to explore community perceptions. Findings reveal that willingness is shaped by economic benefits, cultural attachment, sustainability awareness, and social networks, while readiness depends on knowledge, skills, resources, and commitment. Despite strong motivation and cultural pride, barriers such as limited infrastructure, generational disengagement, and insufficient training hinder full participation. This study contributes to the literature by highlighting the dual role of economic incentives and cultural authenticity in motivating participation, offering practical insights for policymakers and tourism planners to foster inclusive and sustainable cultural heritage tourism.